The relationship of the running distances of the teams participated in the Fifa Women World Cup with the age and estimated oxygen consumption capacities - Karakus, M.; Marangoz, I. (International Journal of Applied Exercise Physiology, 2020)
Background and Study Aim: The purpose of this study is to examine the relationship of the running distances of the teams participated in the FIFA Women World Cup age and estimated oxygen consumption capacities. Material and Methods: The average values of the matchesthey played during the organization were taken in calculating the running distances of these teams. SPSS 22.0 software was used to evaluate the data. Results: According to the research results, the average age of the teams participated in the event was 26,11±3,92, the oldest team was the US team with the average age of 28,69±4,23, the average running distance of the athletes was 104,13 km. -6,94 km., the teams having the longest running distance were Sweden and Canada with 109,5 km. -7,3 km., the team having the shortest running distance was Nigeria with 95,75 km. -6,38 km. VO2 Max average of the teams was 40,44 ml/kg/min. The highest VO2 Max was Sweden and Canada`s teams with 43,11 ml/kg/min, and the lowest was Nigeria`s with 36,26 ml/kg/min. It wasdetermined that the relationship between the team running averages, athletes running averages and estimated maximum oxygen capacity was positive, hence, high oxygen capacity affects team running average and athlete running average in the direction of increase.Conclusions: According to the result of the study, it can be stated that there is a significant relationship between performance, VO2max and age, thereby low average age affects team running average and individual performance positively.